Continuous versus intermittent electrical stimulation of beef carcasses and their effect on hot-boned Muscle-pH decline - J.E. Bowles; Melvin C. Hunt; J.L.A. Kendall; M. Lyon; Curtis L. Kastner; Michael E. Dikeman (Kansas Agricultural Experiment Station Research Reports, 1981)
Short bursts of electricity (intermittent electrical stimulation) to beef carcasses accelerated pH decline and the onset of rigor mortis more than continuous stimulation did.
Keywords: Cattlemen' s Day; 1981; Report of progress (Kansas State University. Agricultural Experiment Station); 394; Beef; Electrical stimulation; pH; Hot-boned